1986
DOI: 10.1073/pnas.83.11.4016
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus immediate early infected-cell polypeptide 4 binds to DNA and promotes transcription.

Abstract: In herpes simplex virus (HSV)-infected cells, there is a sequential expression of viral genes. In vivo experiments have implicated the Mr 175,000 immediate early protein ICP4 (infected-cell polypeptide 4) in the regulation of viral RNA synthesis, but the mechanism whereby ICP4 regulates transcription of viral genes is at present unknown. In this report we describe experiments with an in vitro transcription system and a purified preparation of ICP4 (estimated 5% of total protein). Using DNA from the HSV glycopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
61
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 46 publications
5
61
0
Order By: Relevance
“…The IE protein ICP4 is essential for viral infection because it is required to activate the transcription of the early and late genes (11,37). Consistent with its ability to bind to viral DNA (3,33), ICP4 is recruited into viral replication compartments containing large amounts of replicating viral DNA (10,28,38). However, prior to the onset of DNA replication, ICP4 in fixed cells has been observed to be distributed diffusely throughout the nucleus, with foci appearing as infection proceeds (10,28,38,46).…”
mentioning
confidence: 92%
“…The IE protein ICP4 is essential for viral infection because it is required to activate the transcription of the early and late genes (11,37). Consistent with its ability to bind to viral DNA (3,33), ICP4 is recruited into viral replication compartments containing large amounts of replicating viral DNA (10,28,38). However, prior to the onset of DNA replication, ICP4 in fixed cells has been observed to be distributed diffusely throughout the nucleus, with foci appearing as infection proceeds (10,28,38,46).…”
mentioning
confidence: 92%
“…Vmw175 is a sequence-specific D N A -b i n d i n g protein which recognizes a number of different sequences of which m a n y contain the consensus A T C G T C (Faber & Wilcox, 1986b;Beard et al, 1986;Michael et al, 1988). The sequence at the cap site of the IE-3 promoter is strongly bound by Vmw175 (Mfiller, 1987).…”
Section: Polypeptide Vmw75 Expressed By H 5 H B C Binds To the Ie-3 Cmentioning
confidence: 99%
“…ICP4 is a nuclear phosphoprotein that acts as a homodimer to activate or repress transcription depending upon the promoter (12,15,26,54,63,67,71). Genetic and biochemical studies have shown that ICP4 binds to DNA and interacts with a component(s) of general RNA polymerase II transcription machinery to activate or repress transcription (2,8,17,29,42,64,65,84). ICP4 forms a tripartite complex with TFIIB and TATA binding protein (TBP) on DNA, interacts with TBP-associated factor 250 (8,84), and promotes the formation of transcription preinitiation complexes on promoters (28).…”
mentioning
confidence: 99%